Expanding the mutation spectrum in ICF syndrome: Evidence for a gender bias in ICF2 - BARIŞ, SAFA (WILEY, 2017)
BackgroundImmunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome is a rare, genetically heterogeneous, autosomal recessive disorder. Patients suffer from recurrent infections caused by reduced levels or absence of serum immunoglobulins. Genetically, 4 subtypes of ICF syndrome have been identified to date: ICF1 (DNMT3B mutations), ICF2 (ZBTB24 mutations), ICF3 (CDCA7 mutations), and ICF4 (HELLS mutations). AimTo study the mutation spectrum in ICF syndrome. Materials and methodsGenetic studies were performed in peripheral blood lymphocyte DNA from suspected ICF patients and family members. ResultsWe describe 7 ICF1 patients and 6 novel missense mutations in DNMT3B, affecting highly conserved residues in the catalytic domain. We also describe 5 new ICF2 patients, one of them carrying a homozygous deletion of the complete ZBTB24 locus. In a meta-analysis of all published ICF cases, we observed a gender bias in ICF2 with 79% male patients. DiscussionThe biallelic deletion of ZBTB24 provides strong support for the hypothesis that most ICF2 patients suffer from a ZBTB24 loss of function mechanism and confirms that complete absence of ZBTB24 is compatible with human life. This is in contrast to the observed early embryonic lethality in mice lacking functional Zbtb24. The observed gender bias seems to be restricted to ICF2 as it is not observed in the ICF1 cohort. ConclusionOur study expands the mutation spectrum in ICF syndrome and supports that DNMT3B and ZBTB24 are the most common disease genes.
Keywords: DNMT3B; ICF syndrome; immunodeficiency; ZBTB24; STEM-CELL TRANSPLANTATION; FACIAL ANOMALIES SYNDROME; CENTROMERIC INSTABILITY; PHOSPHOINOSITIDE PHOSPHATASE; ZBTB24 MUTATIONS; IMMUNODEFICIENCY; DNA; DNMT3B; METHYLATION; FIG4